Preliminary findings on the effects of medication advocacy and daily behavior ratings on prescriber behavior. (27th December 2021) - Coon, Jodi C.; Rapp, John T.; Bush, Helena; Ramey, Erica S.
Abstract: Over a 1‐year period, we trained caregivers to employ a color‐coded daily behavior rating system whereby green denoted a high level of appropriate behavior, yellow denoted a mix of some appropriate behavior and mild problem behavior, and red denoted a high level of problem behavior. We then used these ratings to generate graphs that caregivers brought to their child's prescriber appointments. Preliminary data comparing unconditional and conditional probabilities from 25 prescriber visits with 12 participants indicate prescribers were most likely (a) to decrease psychotropic medication following green ratings, (b) increase psychotropic medication following red ratings, and (c) make no changes following yellow ratings. Across participants, prescribers' decisions matched the color code for 76% of trials. These preliminary findings support continued inclusion of the medication‐advocacy training component to facilitate deprescribing of psychotropic medication within our state‐funded project.